Association between the alga Spirogyra (Zygnemataceae) and heavy metals in sediments of the Chi River Basin in Northeast Thailand - Kroeksakul, Patarapong (2026)
Introduction: Sediments act as major sinks of heavy metals from human activities, while algae such as Spirogyra interact with these sediments through nutrient uptake and biogeochemical cycling. In the Chi River Basin, Spirogyra (“Tao”) plays both ecological and socioeconomic roles, serving as food and a bioindicator of pollution. Objective: To evaluate heavy-metal concentrations in sediments and Spirogyra and assesses their potential human health risks. Methods: Water quality, Spirogyra, and sediment samples from the Chi River Basin were analyzed for heavy metals using ICP-OES, with human health risks assessed by THQ and HI, and sediment contamination evaluated through Igeo, EF, CF, PLI indices. Results: Heavy metals (Cd, Cu, Fe, Mn, Zn) in sediments and Spirogyra from the Chi River Basin were assessed under average water conditions (pH 7.49, EC 497 µS cm–2, NaCl 0.024 %, 24.9 ± 3.52 °C), showing concentrations in algae (Fe > Mn > Zn > Cu > Cd) with THQ and HI < 1 indicating low health risk, while sediments (Mn > Fe > Zn > Cu > Cd) exhibited Igeo < 0, EF < 2, CF < 1 except for Fe (CF = 8.31), PLI < 1, and significant correlations between Mn in algae with Cu and Mn in sediments, Cu with Fe in algae, and Cd in algae with Fe in sediments. Conclusions: The findings indicate no significant heavy-metal pollution in sediments or Spirogyra from the Chi River Basin. However, due to elevated Fe contamination in sediments, periodic monitoring is recommended to safeguard ecological and food safety.